PENGELOLAAN KARYAWAN PRAMUSAJI PADA SPICE RESTAURANT MAYANG SARI BEACH RESORT BINTAN KEPULAUAN RIAU - Sinaga, Afriris Melfrida; Arief, Andi M. Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research aims to know : (1) Management of waiters at spice restaurant Mayang Sari Beach Resort Bintan Kepulauan Riau; (2) Management efforts to improve the Management of Waiters at Spice Restaurant Mayang Sari Beach Resort Bintan Kepulauan Riau. Research design using descriptive qualitative. Research subjects use key informant and additional informant. The jey infromant is head of human resources department (HRD) and additional informant is waiters at spice restaurant. The data collection technique used observation, documentation, interviews and documents. Studies using the theory of Miles and Huberman (1992) as a concept.The results of this researchs indicate that the management of waiter not efficient. Management efforts to improve the management of waiters at spice restaurant not accordance with the planning, organizing, actuating and controlling. This happens because the management does not know the abolity of the waiters.Keywors : Management, Waiters, Restaurant, Bintan